Comparative Effectiveness of Infliximab and Adalimumab in Crohn's Disease and Ulcerative Colitis. Issue 4 (April 2016) - Ananthakrishnan, Ashwin N.; Cagan, Andrew; Cai, Tianxi; Gainer, Vivian S.; Shaw, Stanley Y.; Savova, Guergana; Churchill, Susanne; Karlson, Elizabeth W.; Kohane, Isaac; Liao, Katherine P.; Murphy, Shawn N.
Abstract : Background: The availability of monoclonal antibodies to tumor necrosis factor α has revolutionized management of Crohn's disease (CD) and ulcerative colitis. However, limited data exist regarding comparative effectiveness of these agents to inform clinical practice. Methods: This study consisted of patients with CD or ulcerative colitis initiation either infliximab (IFX) or adalimumab (ADA) between 1998 and 2010. A validated likelihood of nonresponse classification score using frequency of narrative mentions of relevant symptoms in the electronic health record was applied to assess comparative effectiveness at 1 year. Inflammatory bowel disease–related surgery, hospitalization, and use of steroids were determined during this period. Results: Our final cohort included 1060 new initiations of IFX (68% for CD) and 391 of ADA (79% for CD). In CD, the likelihood of nonresponse was higher in ADA than IFX (odds ratio, 1.62 and 95% CI, 1.21–2.17). Similar differences favoring efficacy of IFX were observed for the individual symptoms of diarrhea, pain, bleeding, and fatigue. However, there was no difference in inflammatory bowel disease–related surgery, hospitalizations, or prednisone use within 1 year after initiation of IFX or ADA in CD. There was no difference in narrative or codified outcomes between the 2 agents in ulcerative colitis. Conclusions: We identified a modestly higher likelihood of symptomatic nonresponse at 1 year for ADA compared with IFX in patients with CD. However, there were no differences in inflammatory bowel disease–related surgery or hospitalizations, suggesting these treatments are broadly comparable in effectiveness in routine clinical practice. Abstract : Article first published online 2 March 2016.